Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1038/ejhg.2012.182
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing age-specific genetic effects on human extreme age survival in cohort-based longitudinal studies

Abstract: The analysis of age-specific genetic effects on human survival over extreme ages is confronted with a deceleration pattern in mortality that deviates from traditional survival models and sparse genetic data available. As human late life is a distinct phase of life history, exploring the genetic effects on extreme age survival can be of special interest to evolutionary biology and health science. We introduce a non-parametric survival analysis approach that combines population survival information with individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Many other mechanisms exist that can lead to bias in MR, as has been described in detail elsewhere. Fourth, SNPs can appear to be outliers not through being pleiotropic, but through other mechanisms, such as population stratification (association of alleles with phenotypes being confounded by ancestral population), canalisation (developmental compensation to a genetic change) 2,35 , or the influence on phenotype being changeable across the life course 36 . Fifth, since MR-TRYX uses the resource from MR-Base, it is recommended that the user acknowledge the limitation and restriction of MR-Base 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Many other mechanisms exist that can lead to bias in MR, as has been described in detail elsewhere. Fourth, SNPs can appear to be outliers not through being pleiotropic, but through other mechanisms, such as population stratification (association of alleles with phenotypes being confounded by ancestral population), canalisation (developmental compensation to a genetic change) 2,35 , or the influence on phenotype being changeable across the life course 36 . Fifth, since MR-TRYX uses the resource from MR-Base, it is recommended that the user acknowledge the limitation and restriction of MR-Base 10 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that 25 percent of the variability associated with longevity is explained by genetic contributions (Hjelmborg et al, 2006;Deelen et al, 2014). The genetic profiles associated with longevity have increasing influence with advanced age (Hjelmborg et al, 2006;Tan et al, 2012). A recent meta-analytic GWAS study confirmed the role of the previously identified APOE locus in longevity and identified an additional region on chromosome 5q33.3 associated with survival beyond 90 years of age (Deelen et al, 2014).…”
Section: Genetics Of Longevity and Reduced Cancer Burden In The Oldesmentioning
confidence: 95%
“…Many other mechanisms exist that can lead to bias in MR, as has been described in detail elsewhere. Fourth, SNPs can appear to be outliers not through being pleiotropic, but through other mechanisms, such as population stratification (association of alleles with phenotypes being confounded by ancestral population), canalization (developmental compensation to a genetic change) 2,41 , or the influence on phenotype being changeable across the life course 42 . Fifth, since MR-TRYX uses the resource from MR-Base, it is recommended that the user acknowledge the limitation and restriction of MR-Base 10 .…”
Section: Discussionmentioning
confidence: 99%